2017
DOI: 10.1021/acsomega.7b00416
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Mitochondrial Localization of a Goniothalamin Fluorescent Derivative

Abstract: A fluorescent 2,1,3-benzothiadiazole-containing goniothalamin derivative, BTD−GTN (1), has been synthesized and successfully tested in bioimaging experiments in live cells. The fluorescent compound proved to be capable of transposing the cell membranes, indicating its subcellular localization. The use of the benzothiadiazole core as the fluorophore revealed the favored localization of the GTN analogue 1 in the cytoplasm of live cells, preferentially in the mitochondria, in line with previous results that indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…A study conducted by Boonmuen et al, 2016 found that 5-acetyl goniothalamin (5GTN), a natural derivative of GTN was more potent than GTN in mediating the toxicity towards MCF-7 and MDA-MB-2 breast cancer cells (27). Besides, a uorescent 2,1,3-benzothiadiazole-containing goniothalamin derivative, BTD − GTN (1) hybrid, was successfully synthesised in an investigation to gain insights into the subcellular localisation and mechanism of action of MDA-MB-231 cells, which might involve a cascade of events, starting with their interaction with mitochondria (29). In a recent study, a polymeric nanosystem, in which the racemic mixture of GTN (rac-GTN) was encapsulated in pH-responsive acetalated dextran (Ac-Dex) nanoparticles (NPs), has been developed to improve the pharmacokinetic behaviour and selectivity of GTN against cancer cells including MCF-7 and MDA-MB-231 cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Boonmuen et al, 2016 found that 5-acetyl goniothalamin (5GTN), a natural derivative of GTN was more potent than GTN in mediating the toxicity towards MCF-7 and MDA-MB-2 breast cancer cells (27). Besides, a uorescent 2,1,3-benzothiadiazole-containing goniothalamin derivative, BTD − GTN (1) hybrid, was successfully synthesised in an investigation to gain insights into the subcellular localisation and mechanism of action of MDA-MB-231 cells, which might involve a cascade of events, starting with their interaction with mitochondria (29). In a recent study, a polymeric nanosystem, in which the racemic mixture of GTN (rac-GTN) was encapsulated in pH-responsive acetalated dextran (Ac-Dex) nanoparticles (NPs), has been developed to improve the pharmacokinetic behaviour and selectivity of GTN against cancer cells including MCF-7 and MDA-MB-231 cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Bioimaging experiments. The bioimaging experiments were performed in a similar manner to a procedure which have already been published elsewhere [65]. Cells were seeded on 13 mm round glass coverslips on the bottom of a 24-well plate and allowed to adhere overnight.…”
Section: Methodsmentioning
confidence: 99%
“…37 For instance, reactive oxygen species (ROS) imbalances may be a consequence of specific mitochondrial labelling by a new fluorophore, but this issue is not addressed when a new mitochondrial marker is published, unless the bioprobe is developed to detect ROS, as described in several and recent examples. [38][39][40][41][42][43][44][45][46][47][48] We have already disclosed some mitochondrial markers such as fluorescent peptoids, 49 lapachone-based structures, 50 Goniothalamin derivative, 51 multicomponent adducts 52 and benzothiadiazole derivatives. 53 2,1,3-Benzothiadiazole (BTD) is a new class of fluorescent cell markers, as we have disclosed elsewhere.…”
Section: Introductionmentioning
confidence: 99%